TikTok Content Analysis for Strengthening Stunting PreventionEducation Systems - Agustin Putri Rahayu; Rea Ariyanti; Eka Putri Rahayu; Muhamad Zakki Saefurrohim (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Stunting presents significant public health challenges requiring comprehensive prevention strategies. Digital health education has emerged as an effective approach to strengthen health systems and community engagement. TikTok, as a widely accessible social media platform, offers potential for delivering evidence-based stunting prevention education. Objective : This study analyzes stunting education content on TikTok to provide recommendations for optimizing digital health communication strategies in achieving SDGs. Research Methods/ Implementation Methods : Content analysis was conducted on TikTok videos with #preventstunting hashtag posted within six months. The analysis examined 50 highest- engagement videos (final dataset) and identified top 10 most popular videos. Systematic coding analyzed video attributes (duration, music, text display, posting age), audience responses, target demographics, creator backgrounds, and content characteristics (message types, information density, sentiment). Results : Final dataset characteristics revealed optimal attributes: 16-60 second duration, TikTok music integration, explanatory text overlays, 31-90 days posting history, general public targeting, and diverse creator backgrounds. Top 10 popular videos showed similar patterns with extended posting duration (90-180 days), healthcare professional involvement, and multi-sentiment approaches (empathy, humor, fear). Prevention-focused messages with 1-2 key information points generated highest engagement. Recommended video framework includes 60-second duration, music and subtitle integration, active audience interaction, multi-sectoral creators, prevention messaging with 1- 2 focal points, and strategic sentiment use. Creativity, quality, and simplicity emerged as critical engagement factors. Conclusion/Lesson Learned : TikTok demonstrates significant potential for strengthening health system communication strategies in stunting prevention education. Video characteristics substantially influence audience engagement, with simple, informative, and creative content generating optimal responses. This digital platform can enhance health promotion accessibility and reach, contributing to SDG achievement through innovative community-level interventions.